فاعلية برنامج إرشادي عقلاني انفعالي في تحسين مستوى الاتزان الانفعالي لدى مدمن المخدرات: دراسة ميدانية في مستشفى فرانتز فانون في البليدة - حاج قويدر، أسماء; مرصالي، حورية (مؤسسة كنوز الحكمة للنشر والتوزيع, 2023)
تهدف الدراسة الحالية إلى معرفة مدى فاعلية برنامج إرشادي عقلاني انفعالي في تحسين مستوى الاتزان الانفعالي لدى مدمن المخدرات، حيث شملت عينة الدراسة 5 أفراد من نزلاء مصلحة مكافحة الإدمان بمستشفى فرانتز فانون بالبليدة، كانوا في مرحلة علاج، حيث تم اختيارهم بطريقة قصدية. تم تطبيق مقياس الاتزان الانفعالي لمحمد كمال حمدان في القياس القبلي، وتطبيق البرنامج الإرشادي المستند لنظرية الإرشاد النفسي لألبرت اليس في الإرشاد العقلاني الانفعالي والذي ضم 8 جلسات. تم حساب المتوسطات الحسابية للاتزان الانفعالي قبل وبعد تطبيق البرنامج، اختبار T للفروق بين القياسين القبلي والبعدي وهذا باستخدام البرنامج الإحصائي SPSS... وأظهرت النتائج إلى وجود فروق ذات دلالة إحصائية بين القياسين القبلي والبعدي في مقياس الاتزان الانفعالي، مما يدل على فاعلية البرنامج الإرشادي في تحسين مستوى الاتزان الانفعالي لدى مدمن المخدرات. This study aims at identifying the extent of effectiveness of a guiding program in improving the drugs addicts’ emotional stability. The study sample includes five individuals, under therapy, at the service of fighting addiction at the hospital of Frantz Fanon in Blida. They’ve been intentionally chosen. Mohammed Kamel Hamdan’s Emotional Stability Scale has been applied in the pre-measurement phase, and the guiding program has been applied, on the basis of Albert Alice’s psychological guidance theory, in the mental emotional guidance, which has included eight sessions. The arithmetic averages of the emotional stability have been calculated before and after applying the program. (T) Exam has been operated on the differences between the pre and post measurement phases using the Statistical Pack for Social Sciences (SPSS). The results have demonstrated the existence of differences with a statistical significance between the pre and post measurements in the emotional stability scale, which signifies the guiding program effectiveness in improving the drugs addicts’ emotional stability level.
Keywords: السلوكيات السلبية -- ظاهرة الإدمان -- إدمان المخدرات -- مستشفى فرانتز فانون